2021
DOI: 10.21595/jve.2021.21944
|View full text |Cite
|
Sign up to set email alerts
|

Ensembled mechanical fault recognition system based on deep learning algorithm

Abstract: Primary detection and removal of mechanical fault is vital for the recovery of mechanical and electrical equipment. The conventional mechanical fault recognition modules are not able obtain highly sensitive feature attributes for mechanical fault classification in the absence of prior knowledge. The fault diagnosis via data-driven methods have become a point of expansion with recent development in smart manufacturing and fault recognition techniques using the concept of deep learning. In this work, a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…With the gradual deepening of the application of information technology in power generation enterprises, large-scale electric equipment has achieved some results that can be practically applied in life management and prediction, equipment reliability technology, equipment condition monitoring, and fault diagnosis technology. Literature [17] combined with artificial intelligence algorithms to conceive a mechanical fault identification and analysis model, and in the fault identification test, compared with the traditional method, the identification accuracy has been improved to a certain extent. Literature [18] reveals the performance of electrical equipment fault identification and detection technology based on computer vision method through example analysis, realizes low-cost transmission line fault detection, and effectively reduces the operation risk of power plants.…”
Section: Introductionmentioning
confidence: 99%
“…With the gradual deepening of the application of information technology in power generation enterprises, large-scale electric equipment has achieved some results that can be practically applied in life management and prediction, equipment reliability technology, equipment condition monitoring, and fault diagnosis technology. Literature [17] combined with artificial intelligence algorithms to conceive a mechanical fault identification and analysis model, and in the fault identification test, compared with the traditional method, the identification accuracy has been improved to a certain extent. Literature [18] reveals the performance of electrical equipment fault identification and detection technology based on computer vision method through example analysis, realizes low-cost transmission line fault detection, and effectively reduces the operation risk of power plants.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence is a strategic technology that leads the future, and the world's major developed countries take the development of artificial intelligence as a major strategy to enhance national competitiveness and maintain national security. Therefore, each big country is seizing the major strategic opportunities for the development of AI in their own countries, taking the development of AI as one of the indicators of a country's comprehensive national power and raising the development of AI in their own countries to the strategic issues of the country [4][5]. In addition, in the China New Generation Artificial Intelligence Science and Technology Industry Development Report 2021 released by Pujiang Innovation Forum, it is shown that 16 countries around the world have released national AI development strategies or plans one after another, and there are at least 18 other countries that are preparing to formulate AI development plans.…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned ML methods result in a satisfactory classification, especially, SVM proved to provide a high accuracy in research conducted in [14]. In addition, a significant amount of research has been performed on artificial intelligence-based fault diagnosis in pumps [15]. However, the related algorithms classify data based on manually extracted features, which may not be the best for the classification of faults as it requires expertise in manual data analysis.…”
Section: Introductionmentioning
confidence: 99%